The dialog between psychoanalysis and neuroscience: what does philosophy of mind say? - Cheniaux,Elie (2014)
Objective: To briefly review how the main monist and dualist currents of philosophy of mind approach the mind-body problem and to describe their association with arguments for and against a closer dialog between psychoanalysis and neuroscience.Methods: The literature was reviewed for studies in the fields of psychology, psychoanalysis, neuroscience, and philosophy of mind.Results: Some currents are incompatible with a closer dialog between psychoanalysis and neurosciences: interactionism and psychophysical parallelism, because they do not account for current knowledge about the brain; epiphenomenalism, which claims that the mind is a mere byproduct of the brain; and analytical behaviorism, eliminative materialism, reductive materialism and functionalism, because they ignore subjective experiences. In contrast, emergentism claims that mental states are dependent on brain states, but have properties that go beyond the field of neurobiology.Conclusions: Only emergentism is compatible with a closer dialog between psychoanalysis and neuroscience.